ATTENUATION OF PULSE PRESSURE AMPLIFICATION IN ELEMENTARY SCHOOL-AGED PATIENTS WITH COMPLETE TRANSPOSITION OF GREAT ARTERIES AFTER ARTERIAL SWITCH OPERATION. (June 2018) - Murakami, T.; Shiraishi, M.; Takeda, A.; Murakami, T.
Abstract : Objective: We previously reported damaged distensibility of ascending aorta in patients with complete transposition of great arteries after an arterial switch operation (ASO). It resulted in increase of pulse pressure in ascending aorta. Therefore, we examine the pulse pressure amplification in the patients. Figure. No caption available. Design and method: We enrolled 12 patients aged 4–9 years old, who had undergone ASO for complete transposition. A pressure sensor mounted catheter recorded pressure waveforms in ascending and descending aorta. The pressures were compared with those of age-matched 28 patients with a normal aortic arch. Results: The patient's age was 6.4 ± 1.0 years and they underwent the ASO at 0.04 ± 0.02 years. Table demonstrated blood pressure data. The pulse pressure in ascending aorta is elevated and the pulse pressure amplification defined as pulse pressure in descending aorta minus pulse pressure in ascending aorta was significantly decreased in patients with complete transposition after ASO (t = 2.97, p = 0.0052). Conclusions: Pulse pressure amplification is attenuated in patients after ASO and it could cause the future cardiovascular disease.